PREVALENCE OF DIABETIC FOOT IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Conference Zone, 2022)
The purpose of the study : to assess the prevalence of diabetic foot syndrome (DFS) in patients with type 2 diabetes mellitus among the adult population in the Samarkand region for 2021.